DETEKSI DINI PERILAKU KORUPTIF MELALUI ANALISIS PERILAKU MENYONTEK (CHEATING) PADA MAHASISWA AKUNTANSI - Muhammad Ikbal (JURNAL PENDIDIKAN AKUNTANSI, 2014)
This study examines cheating behaviors among 1.839 accounting students at Economic Faculty, University of Mulawarman, Samarinda. The quantitative approach using structural equation model with PLS, examined the role of; 1) gender, academic performance as well as personal characteristics; 2) deterrent, alienation and neutralization as well as attitude characteristics; 3) and motivation and amotivation as well as motivation characteristics; 4) and prior cheating as well as cheating behavior. PLS analysis was used to analyze the data and descriptive statistics were employed to summarize the information. Findings suggest that students with a high GPA, deterrents and motivations may be less likely to cheat. Also the results indicate that there are significant relationships between academic performance, deterrents, neutralization and amotivation with prior cheating behaviour. Research implication; since this study concerns with accounting students there is a need for intensified efforts to educate students early in their academic careers as to the standard of conduct expected of all members of the profession in order to affect their behavior cheating